A STUDY ON THE IMPLEMENTATION OF FLASHCARDS IN TEACHING VOCABULARY - Budiman, Teguh; Manurung, Konder; Maf'ulah, Maf’ulah (e-Journal of ELTS (English Language Teaching Society), 2023)
The objectives of this research are to describe how the implementation of Flashcards in teaching vocabulary and to describe how is students’ vocabulary mastery is after the implementation of Flashcards. The study applied qualitative design that implemented the Library Research Method. The data were collected from scientific writings on implementing Flashcards in teaching vocabulary between 2011 and 2021. The scientific writing was found on the internet. The data were analyzed using content analysis based on Wright (1989). There are nine scientific writings as the data. The results of data analysis showed that implementing Flashcards in nine different studies was carried out using many methods. Some researchers refer to expert recommendations using Flashcards. Buttner (2007), Budden (2013), Allen (1983), Read (2013), Wright (1989), and Harmer (2007). All studies show that students' vocabulary increases after applying Flashcards in their research. Flashcards have some impact on students. For example, Flashcards increase students' motivation to learn vocabulary, students easily understand the material, students can make simple sentences, students acquire new vocabulary, students' vocabulary increases, and students can understand the material. The increase in students' vocabulary is caused by several factors, namely the amount of treatment given, class conditions, and the strategies used by the teachers to overcome students' vocabulary weaknesses.